Indonesian Mental Clause and Its Translation Directions in English - Made Susini; I Nengah Sudipa; I Nyoman Suparwa; Ida Ayu Made Puspani (The Doctoral Studies Program of Linguistics of Udayana University, 2019)
Mental clause, as a grammatical realization used to express experience of ourconsciousness of the world, is commonly found in the text of meditation. This type of text iswritten to persuade people to act in a particular way as suggested by the speaker or writer. Thisresearch is aimed at exploring how the mental clause in Indonesian text is re-contextualized toconvey the same meaning in English. The source language text is a text of meditation entitledButir-Butir Kebijaksanaan: Titian Hidup Sehat dengan Meditasi Bio-Energi Ratu Bagus (IdaPandita Mpu Nabe Parama Daksa Natha Ratu Bagus, 2012) and the target language text is itstranslation entitled Pearls of Wisdom: The Path of a Healthy Life with Ratu Bagus Bio-EnergyMeditation (Stacey, 2014). Knowing that translation is re-contextualization (House, 2015) andusing Systemic Functional Linguistics (Halliday & Matthiessen, 2014) and translation strategies(Malone, 1988) as the main theories, this study focuses on the directions of the translation of themental clause from Indonesian into English and on the translation strategies leading to thedirections. The research result shows that the mental clause of the Indonesian text can berendered into various clause types, including mental clause and non-mental clause. It can also berendered into a form of nominalization. The strategies which condition the directions include thestrategies of equation, reordering, diffusion and condensation.